Acúmulo de nutrientes nos frutos e teor foliar na pimenta do-reino - Dalazen, Jessica Rodrigues (2019)
The Balck pepper is a nutrient-demanding crop, especially during the reproductive stage. Knowing the foliar content, as well as the curve of nutrient accumulation in the peppercorns, helps in the recommendation and adjustment of the fertilization program of the crops, improving the sustainability of the activity. The objective of this study was to establish nutrient uptake curves in black pepper curls throughout the reproductive period, to determine the content and accumulation of nutrients in different parts of the curls (grain, bark and stalk / fruit and peduncle) of black pepper harvested at two maturation stages (green peel color / red house color), as well as foliar content throughout the year. The experiments were carried out in commercial crop of Piper nigrum L., of the variety Bragantina, in São Mateus, Espírito Santo, Brazil. The experiments of the first experiment were conducted following a completely randomized design, in plot arrangement in time. The treatments consisted of different sampling times. For the analysis of the clusters, a total of 11 collections were performed in the first reproductive cycle and 09 in the second cycle. In each evaluation, nine clusters were randomly collected, forming compound samples every three, thus three replications. For analysis of leaf tissue content, a total of 20 samplings were performed throughout the year, each sample was composed of 40 fresh leaves with three replicates, per sampled period. The materials of all the tests were dry and the macronutrients and micronutrients contents were obtained in the laboratory. Based on the results of the first and second chapters, it was observed that the most abundant macronutrients in the curls and leaves of the black pepper were N, K and Ca, and the micronutrients were Fe, Mn and B. At leaf content of nutrients fluctuated during the year. The accumulation of dry mass in the pepper fruit was similar in both cycles, adjusting to the linear and quadratic model. In the third chapter, it was observed that the nutrients most accumulated in the peppermint fruit were N, K, Ca, Mg, P, S, Mn, Fe, B, Zn and Cu. In the peduncle were: K, N, Ca, Mg, P, S, B, Fe, Zn, Mn and Cu. The order of nutrients accumulated in the grain was: N, xii Ca, K, P, S, Mg, Mn, B, Fe, Zn and Cu. Already in the shell was K, N, Ca, Mg, P, S, B, Fe, Zn, Mn and Cu. E in the peduncle K, Ca, N, Mg, P, S, B, Fe, Zn, Mn and Cu.